Hemoglobin E detection using PCR with confronting two-pair primers - Sorasak Intorasoot (2018)
Objective: To develop and apply the polymerase chain reaction with confronting two-pair primers (PCR-CTPP) for detection and identification of hemoglobin E (Hb E). Material and Method: Fifty unrelated northern Thais were included in the present study. DNA was extracted from peripheral blood mononuclear cells and targeted to amplify by PCR-CTPP. The amplified product was analyzed and compared with the reference hemoglobin electrophoresis and polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) analysis. Results: The results validated a completely concordant among these three methods consisting of 74%, 24%, and 2% identified as normal, heterozygous, and homozygous Hb E type, respectively. Conclusion: Successful Hb E genotyping by PCR-CTPP was introduced. It allows for confirming and simultaneously detection with other thalassemia mutations.